Immunological Fingerprinting Method for Differentiation of Serum Samples in Research-Oriented Biobanks - Beaumont, Katy (American Society for Microbiology (ASM), 2010)
An immunoenzymatic serum fingerprinting method was developed to establish a serum sample fingerprint based on IgG titers obtained with three different antigens. Three widely expressed antigens were selected for their capacity to induce long-lasting humoral immune responses. This fingerprinting method may be used to differentiate between two serum samples and to determine whether they come from the same primary blood specimen. The method showed a specificity of 99.5%. This method is suitable as a quality control method for biobanked serum samples.